A NEXUS BETWEEN FINANCIAL DEVELOPMENT AND RENEWABLE ENERGY CONSUMPTION - Zaidi, Fareeha; Riaz, Dr. Salman; Saleem, Zubair (The journal of contemporary issues in business and government, 2021)
The purpose of the present study is to explore the impact of financial development on renewable energy consumption. The period of study is from 1980 to 2018. Economic growth plays a mediating role in the nexus between energy consumption and financial development. The transmission and distribution losses are the moderator between economic growth and renewable energy consumption in the structural model. For developing economies like Pakistan, estimation for energy demand without considering financial development would provide an inaccurate picture. Zivot-Andrews unit root test has been applied under the structural break method to check the stationary property of variables. The study is employing Simple time-series regression analysis to find out the relationship between the variables. The results of the empirical research indicate that financial development and economic growth have a significant impact on renewable energy consumption, and the findings of the economic growth equation suggest that there is a significant impact of financial development and investment on economic growth in Pakistan. The study results urge the attention of policymakers in Pakistan to design a comprehensive energy conservation policy to minimize the consequences of massive energy consumption and energy export-driven revenue by adding financial development and investment as explanatory determinants in the energy demand function..